STUDI KELAYAKAN USAHA PRODUK TEH CELUP CASCARA-JAHE MERAH - Indah Nalurita; Fuad Sauqi Isnain (Faculty of Agriculture Science & Technology, 2022)
The development of a new product entails a business feasibility study. Study of business feasibility is a research on a business plan to analyze the feasibility of business and to estimate the maximum profit for an indefinite time. The aim of this study was to determine the feasibility of business development from financial aspect and predict the profit that will be obtained in the development of red ginger tea dip product. The financial feasibility were analyzed using Net Present Value (NPV), Benefit Cost Ratio (B/C Ratio), Internal Rate of Return (IRR), Break Event Point (BEP) and Payback Period (PBP). The results showed that the development of red ginger tea dip product was feasible based on marketing analysis with the NPV IDR 388.277.344; IRR 48%l; B/C ratio 1.13; BEP 97.990.767 units; and PBP 1.7 years.